THE LEARNING AND STUDY STRATEGIES INVENTORY (LASSI) TOOL FOR DEVELOPING STUDENTS’ METACOGNITION SKILLS AND STRATEGIC STEERING IN MEDICAL SCHOOL - Ullal, Aruna; Ullal, Gautam (PUPIL: International Journal of Teaching, Education and Learning, 2024)
Medical education poses significant challenges for several students, especially given the rapidly evolving medical science curriculum. Further, the intensity increases as they prepare for the high-stakes term exams and the United States Medical Licensing Examination (USMLE). As per the Association of American Medical Colleges (AAMC) Student Records System data from medical school registrars between 1997-1998 and 2016-2017, medical students exited medical school for nonacademic reasons rather than academic reasons. The national total attrition rate, ranging this 20-year period, remained averaging 3.2% (Association of American Medical Colleges, 2022). Therefore, recognizing areas of strengths and opportunities in both cognitive and noncognitive skills for achieving targeted mediation during the early years of medical education is critical for ensuring student success. One valuable diagnostic tool we have found effective is the Learning and Study Strategies Inventory (LASSI), a 60-item tool with ten scales designed to evaluate the "Skill component," the "Will component," and the "Self-regulation component" of strategic learning. Our primary strategy has been to investigate the benefits of utilizing the LASSI tool for early recognition of metacognitive skills and providing tailored learning approaches to remediate the overall progress in successfully completing medical education by future clinicians.